Double Whammy: Concomitant Acute Type B Aortic Dissection and Acute Pulmonary Embolism - Gouran, Amirkhosro (Vasc Specialist Int, 2020)
The concomitant occurrence of acute type B aortic dissection (TBAD) and acute pulmonary embolism (PE) is a rare but challenging condition. Although anticoagulation therapy is essential in the treatment of PE, it may increase the risk of aortic rupture and bleeding complications. We herein describe a patient with acute TBAD complicated by PE, which was successfully treated with early thoracic endovascular aortic repair (TEVAR) followed by anticoagulation. The present case report demonstrates that early TEVAR not only treats the aortic pathology but also allows the safe initiation of anticoagulation therapy.